THE EFFORT OF CHINA TO RESTRAIN THE U.S. HEGEMONY IN FINANCIAL SECTOR - Riana Yunita (HI 16 UMY 153, 2016)
*153 The economy of China is growing rapidly that place China as the fastest growing economic country in the world. Deng Xiaoping is launched the reform movement that changes China from a poor country to an industrialized one in 1978. As we know that the United States hegemony is very powerful with its alliances around the world and its strong influences in the World Bank and the IMF. However, the rise of China become extraordinary issue that some of the scholars predict it can decline US hegemony. China, even though become one of the members of the World Bank and IMF, felt that it could not have bigger role in the World Bank and IMF because not as one of the Western countries. Therefore, China seeks to gain more roles in international world by establish some economic initiatives such as Asian Infrastructure Investment Bank that include in Chinaâ€™s project to restrain the U.S. hegemony in structural power. China proposed the new Bank to help countries in the world that needs more infrastructures, especially in Asia-Pacific, which is better known as Asian Infrastructure Investment Bank.The establishment of Asian Infrastructure Investment Bank or AIIB as â€œcompetitor Bankâ€ of the World Bank and IMF can be stated as a response to frustrations because United States blocking an important agreement to increase the resources of the IMF and give developing countries a greater share in decision-making. Along with a New Silk Road project, the AIIB has enlisted to build infrastructure across the continent in order to create a more integrated Asia-Pacific economic cooperation.